Missing medical records: an obstacle to archival survey-research in a rural community in South Africa - L. Wegner; A. Rhoda (AOSIS, 2013)
Keeping good quality medical records is an essential yet oftenneglected part of a health-care practitioner's workload. In South Africa, by lawall health care facilities are required to retain medical records for a minimum ofsix years after the cessation of a patient's treatment. In an archival survey thatwas attempted in a rural community in South Africa, only 39% of the recordsthat were requested were located. The procedure that was followed in order toobtain the records to be included in the survey is briefly described in this paper,highlighting the challenges experienced in four district hospitals in this community.The phenomenon has serious implications not only for the quality of healthcare,incidence of iatrogenic injuries and the future of the health-care practitioner's career, but it also impacts on the ability to conductresearch to inform practice. An aspect that is not often considered is the impact of poor record keeping on the research and teachingcomponent of the broader medical profession.